2022
DOI: 10.1002/admi.202102427
|View full text |Cite
|
Sign up to set email alerts
|

A Durable Fluorine‐Free MOF‐Based Self‐Cleaning Superhydrophobic Cotton Fabric for Oil‐Water Separation

Abstract: It is challenging to fabricate durable and fluorine‐free superhydrophobic surfaces through simple procedures. In this study, a novel fabrication method for constructing robust, wearable, and fluorine‐free superhydrophobic surfaces on cotton textiles has been achieved via in situ growth of zeolitic imidazolate framework‐8 (ZIF‐8) layers followed by polydimethylsiloxane (PDMS) modification. The roughness created by the sheet‐like structure is optimized by tuning the mole ratio between 2‐methylimidazole and zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…This enhanced cytotoxicity can be attributed to the improved cellular delivery capability of Res@ZIF‐8/TA NPs, leading to increased anticancer efficiency of Res. Previous studies have reported that surface modification of ZIF‐8 NPs significantly enhances their biocompatibility with normal cells, facilitating effective drug encapsulation and delivery, thereby greatly improving drug efficacy 26,27 . These findings are consistent with results obtained by Zheng et al 28 and Shearier et al 29 where coating effectively improved the biocompatibility of nanoparticles with normal cells and reduced side effects and toxicity.…”
Section: Resultssupporting
confidence: 90%
“…This enhanced cytotoxicity can be attributed to the improved cellular delivery capability of Res@ZIF‐8/TA NPs, leading to increased anticancer efficiency of Res. Previous studies have reported that surface modification of ZIF‐8 NPs significantly enhances their biocompatibility with normal cells, facilitating effective drug encapsulation and delivery, thereby greatly improving drug efficacy 26,27 . These findings are consistent with results obtained by Zheng et al 28 and Shearier et al 29 where coating effectively improved the biocompatibility of nanoparticles with normal cells and reduced side effects and toxicity.…”
Section: Resultssupporting
confidence: 90%
“…9,10 These concerns have led researchers to explore alternative approaches that prioritize sustainability and minimize adverse environmental impacts. 11 Biobased materials have been investigated as more sustainable solutions for post-treatment in textile finishing. Recently, biobased polyphenolic materials have gained significant attention in the textile industry.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] However, the design and development of functionalized adsorbent materials used in oil-water separation is still a challenge. Various functional materials such as cellulose, 15 graphite, 16 cotton fabrics 17 and sponge 18 have been used widely to separate oil from water. Among them, the three-dimensional (3D) porous sponge has attracted significant attention in the field of oil/water separation owing to its welldeveloped pore structure and large surface area.…”
Section: Introductionmentioning
confidence: 99%